2004
DOI: 10.1177/000312240406900205
|View full text |Cite
|
Sign up to set email alerts
|

The Academic Caste System: Prestige Hierarchies in PhD Exchange Networks

Abstract: E xtensive research demonstrates the importance of departmental prestige for the career prospects of academic professionals. The prestige of the department in which an academic received a PhD consistently ranks as the most important factor in determining the employment opportunities available to those entering the academic labor market. Across a range of academic fields, studies report a high correlation between the prestige of the departments in which academics received their degrees and the prestige of the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
371
0
21

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 485 publications
(411 citation statements)
references
References 52 publications
19
371
0
21
Order By: Relevance
“…Berelson (1960) Hagstrom, 1971, Burris, 2004and Merritt and Reskin, 1997, for the USA). Yet, Berelson (1960) also suggested that inbreeding processes at these universities could be different from other schools, for example those focusing more on teaching, because of the specific organizational environment.…”
Section: H2 -Productivity Hypothesis: "Inbred Faculty Produce Fewer Smentioning
confidence: 99%
“…Berelson (1960) Hagstrom, 1971, Burris, 2004and Merritt and Reskin, 1997, for the USA). Yet, Berelson (1960) also suggested that inbreeding processes at these universities could be different from other schools, for example those focusing more on teaching, because of the specific organizational environment.…”
Section: H2 -Productivity Hypothesis: "Inbred Faculty Produce Fewer Smentioning
confidence: 99%
“…al 2006a;2006b;Borgatti and Everett 1999). Thus, the core / periphery concept in social network analysis captures the extent to which a given graph has a latent core / periphery interaction pattern among actors in the network, and has been implemented across a wide array of substantive contexts, including epidemiology (Jolly et al 2001;Christley et al 2005), small groups (Cummings and Cross 2003), interpersonal networks (Bourgeois and Friedkin 2001), linguistics (Dodsworth 2005), groups in isolated or extreme environments (Johnson, Boster, and Palinkas 2003), networks of creative artists (Uzzi and Spiro 2005), PhD exchange networks (Burris 2004), and knowledge communities of firms (Giuliani and Bell 2005). Table 1 represents an ideal-typical image matrix that reflects a social network conception of a core / periphery structure.…”
Section: World-systems Theory and Network Analysis: A Reviewmentioning
confidence: 99%
“…Cultural inertia, the tendency of communities to cling to a traditional trajectory, is shaped by a complex ecosystem of individuals and groups. These often have highly polarized motivations (i.e., capitalistic commercialism versus knowledge generation versus careerism versus output measurement), and an academic hierarchy that imposes a power dynamic that can suppress innovative practices ( Burris, 2004; Magee & Galinsky, 2008). …”
Section: The Traits and Trends Affecting Modern Peer Reviewmentioning
confidence: 99%